Advances in water and wastewater treatment - Surampalli, Rao Y.; Tyagi, R. D., 1952- (American Society of Civil Engineers, 2004)
Annotation "Advances in Water and Wastewater Treatment provides state-of-the-art information on the application of innovative technologies for water and wastewater treatment with an emphasis on the scientific principles for pollutant or pathogen removal. Described in detail are the practice and principles of wastewater treatment on topics such as: global warming, sustainable development, nutrient removal, bioplastics production, biosolid digestion and composting, pathogen reduction, metal leaching, secondary clarifiers, surface and subsurface constructed wetland, and wastewater reclamation. Environmental engineers and scientists involved in the practice of environmental engineering will benefit from the basic principles to innovation technologies application."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.
Keywords: Water -- Purification.; Sewage -- Purification.; Water -- Purification -- Technological innovations.; Sewage -- Purification -- Technological innovations.; elektronické knihy; electronic books